MULTIDISCIPLINARITY IN THEORY BUILDING: POSSIBILITIES OF COMBINING - Lehtinen, Uolevi (European Scientific Journal, ESJ, 2013)
The article aims to strengthen theoretical development that will hopefully result in more systematic combinations and combined use of present approaches, such as frameworks, models and theories. At the same time this would increase multiple disciplinarity in future research. The objectives of this article are to describe why, when and how to develop theoretically new, combined approaches and illustrate them theoretically and empirically with the help of the former studies. Combining is examined in the connection of multiple disciplinarity. Business administration, especially marketing is used as a theoretical and empirical example area. Methodology is inductive and deductive logic and in the empirical examples surveys, case analysis and secondary data are utilized. This article introduces an insufficiently used but rather promising way, in the long run, to develop new, comprehensive and multiple disciplinary approaches and even paradigms for different disciplines. Consequently, the ultimate message of the article is to stimulate the researchers to put the idea and rationale for combing to the test in their own research field and to build new, combined and comprehensive approaches if possible in the field. This message is a multiple disciplinary one, embracing for example economics, social sciences and political sciences in addition to business administration.